ANTI-INFLAMMATORY ACTIVITY OF TINOCRISPOSIDE BY INHIBITING NITRIC OXIDE PRODUCTION IN LIPOPOLYSACCHARIDES-STIMULATED RAW 264.7 CELLS - Adnan, Adek Zamrud; Taher, Muhammad; Afriani, Tika; Fauzana, Annisa; Imelda Roesma, Dewi; Eka Putra, Andani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of this study was to investigate in vitro anti-inflammatory activity of tinocrisposide using lipopolysaccharides (LPS)-stimulated RAW 264.7 macrophage cells. Tinocrisposide is a furano diterpene glycoside that was isolated in our previous study from Tinospora crispa. Methods: Anti-inflammatory effect was quantified spectrometrically using Griess method by measuring nitric oxide (NO) production after the addition of Griess reagent. Results: The sample concentrations of 1, 5, 25, 50, and 100 Î¼M and 100 Î¼M of dexamethasone (positive control) have been tested against the LPS-stimulated RAW 264.7 cells, and the results showed NO level production of 39.23, 34.00, 28.9, 20.25, 16.3, and 13.68 Î¼M, respectively, and the inhibition level of 22.67, 33.00, 43.03, 60.10, 68.00, and 73%, respectively. Conclusions: From the study, it could be concluded that tinocrisposide was able to inhibit the formation of NO in the LPS-stimulated RAW 264.7 cells in concentration activity-dependent manner, with half-maximal inhibition concentration 46.92 Î¼M. It can be developed as anti-inflammatory candidate drug because NO is a reactive nitrogen species which is produced by NO synthase. The production of NO has been established as a mediator in inflammatory diseases.